(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The aim of the investigation was to study the significance of the level of procalcitonin in the blood serum for the early diagnosis of spontaneous bacterial peritonitis in patients with decompensated cirrhosis of the liver of viral etiology. Results. 120 [64 (53.3%) men and 56 (46.7%) women] patients with cirrhosis of the liver of viral etiology at the age from 30 to 69 years were examined. Of the clinical symptoms, the most common signs of SBP were fever - 36.7%, leukocytosis with the appearance of immature forms of leukocytes - 46.7%, dyspeptic symptoms - 61.7%. In all patients with SBP (n = 60) who emerged in the phase of decompensation of viral cirrhosis, PCT levels were significantly (p = 0.001) higher than in patients of the second group, that is, in uncomplicated patients with SBP (n = 60). When analyzing an increase in the PCT level in blood serum in patients of the first group, the PCT content was observed in the range of 0.5-1.0 ng / ml in 45.0%, in the range of 1.0-2.0 ng / ml in 28.3% and in the range> 2.0 ng / ml in 26.7% of patients. In the second group of observed patients, serum PCT did not exceed 0.2 ng / ml. PCT levels in blood serum were recorded in the range of 0.05–0.1 ng / ml in 18.5% of patients, in the range of 0.1–0.25 ng / ml in 30.0% of patients and in the range 0.25– 0.5 ng / ml in 51.7% of patients. Serum procalcitonin levels are considered a marker for the diagnosis of bacterial infections and are recommended as a marker for early non-invasive diagnosis in patients with spontaneous bacterial peritonitis of viral cirrhosis of the liver.